Stanovništvo Blata na Korčuli (1870-1880) : početak demografske tranzicije - Lazarević, Ivana (Array, 2009)
Analysis has confirmed that Blato followed the major demographic trends observed on the central Dalmatian islands, which, in numerous details, showed sharp dissimilarities from the Dalmatian mainland.